2011
DOI: 10.1080/10934529.2011.598819
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in freshwater fish in the Chihuahua County water reservoirs (Mexico)

Abstract: Water reservoirs in Chihuahua County, Mexico, are affected by some punctual and non-punctual geogenic and anthropogenic pollution sources; fish are located at the top of the food chain and are good indicators for the ecosystems pollution. The study goal was to: (i) determine arsenic concentration in fish collected from the Chuviscar, Chihuahua, San Marcos and El Rejon water reservoirs; (ii) to assess if the fishes are suitable for human consumption and (iii) link the arsenic contents in fish with those in sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The mercury residues in the current study were nearly similar to those (0.11 ± 0.22-0.19 ± 0.09 mg/kg) in fish collected from Italian Coasts (30). Meanwhile, lower Hg values were obtained at 0.014 ± 0.007 mg/kg in the Italian study (38) and 0.017 ± 0.004 and 0.020 ± 0.005 mg/kg in salmon and trout, respectively, in the Norwegian study (34). Because MeHg is harmful to the development of the brain, pregnant women and young children should be especially cautious about exposure to mercury (39).…”
Section: Mercury Residuessupporting
confidence: 85%
See 1 more Smart Citation
“…The mercury residues in the current study were nearly similar to those (0.11 ± 0.22-0.19 ± 0.09 mg/kg) in fish collected from Italian Coasts (30). Meanwhile, lower Hg values were obtained at 0.014 ± 0.007 mg/kg in the Italian study (38) and 0.017 ± 0.004 and 0.020 ± 0.005 mg/kg in salmon and trout, respectively, in the Norwegian study (34). Because MeHg is harmful to the development of the brain, pregnant women and young children should be especially cautious about exposure to mercury (39).…”
Section: Mercury Residuessupporting
confidence: 85%
“…The As residual concentration in marine fish was similar to EFSA ( 33 ) data, which reported a mean value of 1.45 mg/kg after examination of 3,505 different species. In addition, 0.78 ± 0.26 and 0.94 ± 0.31 mg/kg of salmon and trout were collected from the Norwegian fish market ( 34 ). However, As content in the current study was much higher than 0.59–0.69 mg/kg in fish collected from Italian Coasts ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study was conducted by the authors to evaluate arsenic concentrations in fish from Chihuahua County dams and it was found that the arsenic concentration varied through the sampling periods [ 23 ]. However, it should be highlighted that this is the first study done to determine the concentrations of heavy metals (Hg, Cd, Pb) in fish and estimate their weekly intake through the consumption of fish from water reservoirs of Chihuahua County.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that human exposure to high concentrations of some soluble heavy metals affects the central nervous system and may also disrupt the functioning of some organs [5,6]. Studies performed on dams in Chihuahua City reported high concentrations of heavy metals in fishes, an important bioindicator of their presence in the local abiotic environment and representing a health risk due to their ingestion [7,8].…”
Section: Introductionmentioning
confidence: 99%